EFFICACY AND SAFETY OF NICORANDIL FOR PERIPROCEDURAL MYOCARDIAL INJURY IN PATIENTS UNDERGOING PCI - SHAH, SB; KHAN, S; KHAN, MU (Biological and Clinical Sciences Research Journal, 2024)
Coronary artery disease (CAD) remains a leading cause of morbidity and mortality globally, with percutaneous coronary intervention (PCI) being a typical therapeutic approach. Objectives: In this comparative study, we aimed to investigate the efficacy and safety of nicorandil for periprocedural myocardial injury in patients undergoing PCI. Methods: This comparative study was conducted at Ayub Teaching Hospital from September 2023 to December 2023. Data from 90 patients was recruited for the research using inclusion and exclusion screening standards. Our study was performed on 90 patients treated with percutaneous coronary intervention (PCI). Patients from Group 1 were different from those in Group 2. Group A: the critical study parameters will switch between those patients who received nicorandil and Group B: non-nicorandil patients. Baseline demographic data, past medical history, and relevant laboratory values and clinical characteristics were documented for all patients. In addition, an intraoperative laboratory investigation was conducted, including cardiac biomarkers. Results: Research data were drawn from 90 patients whose gender wasn’t a factor based on the research protocol. In Group A, the mean age of the patients was 62 years. Players in group A played for 4 ± 8.5 years. In team B, the players had a slightly longer experience and played for 63. Humans on Earth could do the same, and it could significantly impact future generations: ± 7. 9 years. Of 58 men and 32 women in the control group, there were two persons and persons in the experimental group, respectively. Only one stent differed between the two groups; however, the number was similar. 8 ± 0. 6 mmol/l in the tricorandil group and 1. +9 ± 0 in Case 1. Patients in the Nicorandil group displayed the lowest level of heart problem-causing protein (troponin) at the peak (5. There is a statistically significant 1.8-fold (2 ng/mL versus seven ng/mL) decline in serum lysozyme levels in the group administered rhG-CSF. The treatment group exhibited a substantial increase in haemoglobin levels (t(12) = 3. 74, p-value <0.005) with a mean difference of 0. 5 ± 2 ng/mL. 001, 95% CI: 2. 1 to 3. 5). Conclusion: It is concluded that nicorandil shows positive results for the efficacy (the ability of a drug to bring the desired effect) and safety of the drug in reducing myocardial injury and in maintaining the function of myocardial during percutaneous coronary intervention in patients.